The halal food strategy in Islam: Its theoretical foundations and contemporary applications - Shogar, Ibrahim Adam Ahmed (2017)
Food security and food safety are the major concerns of the globalizing community of today. Food resources in the planet earth must be utilized in a manner that would make it capable of satisfying the increasing needs of successive generations. Food safety and food quality are the major means to meet and maintain the final objectives of security. It is fortunate that both of these problems, i.e. food security and safety matters, can be well addressed by halal food theory as originally conceptualized in Islamic law tradition. This is the basic presupposition that the present paper has tried to examine in two basic parts. In addition to the introductory section, the first part of the paper focuses on the fundamentals of halal food theory, whereby the author has made an analytical study /reflection on key concepts and presented the basic principles of halal food theory as introduced / presented by Islamic tradition. The second part of the paper investigates the increasing interest in „halal‟ in the context of global community. It examines the halal food theory as understood and applied by the contemporary food industry and food business. This includes the basic factors behind the contemporary food surge, its complexities, dynamics, its future trends, progress and challenges. The basic question that has been in mind to guide to the relevant conclusions in both parts of the paper was how the halal food strategy can contribute to deal with the above two major problems of food enterprise, i.e. food security as well as food safety?